2010
DOI: 10.1111/j.1365-2109.2010.02625.x
|View full text |Cite
|
Sign up to set email alerts
|

The anaesthetic-like effect of tea tree oil in common carp Cyprinus carpio L.

Abstract: This study investigated the efficacy of tea tree oil (TTO) as an anaesthetic for common carp, Cyprinus carpio L., by estimation of behaviour changes and responsiveness to being taken out of the water. All applied concentrations (from 0.2 to 0.6 mL L−1) resulted in sedation and immobilization. The lowest effective concentration (induction time ≤3 min, recovery time ≤10 min after 15 min of exposure) was 0.5 mL L−1. Exposure in excess of 30 min at a concentration of 0.5 mL L−1 caused mortality. TTO displayed dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 25 publications
3
17
0
7
Order By: Relevance
“…However, when exposed to 400-600 or 800 μL L −1 EOCA or 300-400 or 500 μL L −1 EOCL, the increasing concentration proportionally decreased the time required for sedation and anesthesia induction. The inverse relationship between the concentration of EO and induction time verified in this study had previously been observed: in R. quelen anesthetized with the EOs of L. alba (Cunha et al, 2010) and A. triphylla ; in Centropomus parallelus Poey, 1860 with the EO of Nectandra megapotamica (Tondolo et al, 2013); and in C. carpio with the EOs of Melaleuca alternifolia and Mentha spicata (Hajek, 2011;Roohi, Imanpoor, 2015).…”
Section: Tab 2 Water Parameters After 8 H Exposure Ofsupporting
confidence: 86%
“…However, when exposed to 400-600 or 800 μL L −1 EOCA or 300-400 or 500 μL L −1 EOCL, the increasing concentration proportionally decreased the time required for sedation and anesthesia induction. The inverse relationship between the concentration of EO and induction time verified in this study had previously been observed: in R. quelen anesthetized with the EOs of L. alba (Cunha et al, 2010) and A. triphylla ; in Centropomus parallelus Poey, 1860 with the EO of Nectandra megapotamica (Tondolo et al, 2013); and in C. carpio with the EOs of Melaleuca alternifolia and Mentha spicata (Hajek, 2011;Roohi, Imanpoor, 2015).…”
Section: Tab 2 Water Parameters After 8 H Exposure Ofsupporting
confidence: 86%
“…Thus, the lower concentrations of each EO that resulted in satisfactory times of anaesthesia induction and recovery and indicated by Pawar et al (2011) for the anaesthesia of seahorses Hippocampus kuda (total length 15.5 cm and weight 11 g). The concentration of 500 µL L -1 of tea tree, recommended here, confers with the dose indicated by Hajek (2011) for anaesthesia of the common carp Cyprinus carpio, weighing 22 g, the only reference found in literature regarding the use of tea tree oil in fish anaesthesia. The use of the same concentrations of each oil to different sizes and species of fish suggests an absence of a relationship between these characteristics with the ideal concentration of the drug, demonstrating that it is important to carry out species-specific studies on the effect of the anaesthetic potential.…”
Section: Resultsmentioning
confidence: 99%
“…A commercial product based on the EO of tea tree is commonly used as a cicatrizant medicine in ornamental fish. Nevertheless, studies about its anaesthetic efficacy in fish are scarce (Hajek, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, eugenol, the main active compound of clove oil, has been reported that it might damage hepatic tissue in mice (17). It has been reported that the essential oils from Oleum malaleucae (18), Ocimum gratissimum (19), and Lippia alba (20) have anesthetic activity in fish. The desirable properties of anesthetic agents in fish should be highly effective and safe.…”
Section: Introductionmentioning
confidence: 99%